ALGORITHMIZATION OF CALCULATION OF STATISTICAL INDICES OF THE PROCESS REPRODUCIBILITY AND ESTIMATION OF CONTRIBUTIONS OF TECHNOLOGICAL STAGES TO QUALITY FORMING OF HARDWARE PRODUCTS OF METALLURGICAL PRODUCTION.. - A. N. Chichko; L. A. Feklistova (Литьë и металлургия)
The method for estimation of  contributions of  the technological cycle different stages in forming of  the hardware products quality, based on indices of  process reproducibility Cp and Сpk,  Cm and Сmk, for different production departments, is offered.